Intensified inundation shifts a freshwater wetland from a CO2 sink to a source. (25th June 2019) - Zhao, Junbin; Malone, Sparkle L.; Oberbauer, Steven F.; Olivas, Paulo C.; Schedlbauer, Jessica L.; Staudhammer, Christina L.; Starr, Gregory
Abstract: Climate change has altered global precipitation patterns and has led to greater variation in hydrological conditions. Wetlands are important globally for their soil carbon storage. Given that wetland carbon processes are primarily driven by hydrology, a comprehensive understanding of the effect of inundation is needed. In this study, we evaluated the effect of water level (WL) and inundation duration (ID) on carbon dioxide (CO2 ) fluxes by analysing a 10‐year (2008–2017) eddy covariance dataset from a seasonally inundated freshwater marl prairie in the Everglades National Park. Both gross primary production (GPP) and ecosystem respiration (ER) rates showed declines under inundation. While GPP rates decreased almost linearly as WL and ID increased, ER rates were less responsive to WL increase beyond 30 cm and extended inundation periods. The unequal responses between GPP and ER caused a weaker net ecosystem CO2 sink strength as inundation intensity increased. Eventually, the ecosystem tended to become a net CO2 source on a daily basis when either WL exceeded 46 cm or inundation lasted longer than 7 months. Particularly, with an extended period of high‐WLs in 2016 (i.e., WL remained >40 cm for >9 months), the ecosystem became a CO2 source, as opposed to being a sink or neutral for CO2 in other years. Furthermore, the extreme inundation in 2016 was followed by a 4‐month postinundation period with lower net ecosystem CO2 uptake compared to other years. Given that inundation plays a key role in controlling ecosystem CO2 balance, we suggest that a future with more intensive inundation caused by climate change or water management activities can weaken the CO2 sink strength of the Everglades freshwater marl prairies and similar wetlands globally, creating a positive feedback to climate change. Abstract : The unequal responses between gross primary production and ecosystem respiration caused a weaker net ecosystem CO2 sink strength as inundation intensity increased in an Everglades short‐hydroperiod wetland. Particularly, with an extended period of high‐WLs in 2016, the ecosystem became a CO2 source, as opposed to being a sink or neutral for CO2 in other years. A future with more intensive inundation caused by climate change or water management activities can weaken the CO2 sink strength of similar wetlands globally, creating a positive feedback to climate change.